SIGNIFICADO Y NECESIDAD EN EL 'TRACTATUS' - Acero, Juan José (Daimon Revista Internacional de Filosofia, 1991)
This paper deals with Wittgenstein´s thesis that both tautologies and contradictions say nothing, a central idea within 'Tractatus' philosophy of logic. By using a possible worlds approach to semantics it is first argued that this thesis encloses a problem- the proposition bipolarity problem, as Wittgenstein called it. Then it is shown how in order to find his way out of it, he had to turn to a theory of natural meaning and to a doctrine concerning the world´s essence both of which remained tacit to a large extent. Finally, a few tractarian thesis concerning the relations between logic and necessity, the limits of languaje and the saying/showing dichotomy are analyzed in the light of these semantic and metaphysical doctrines.